Ակսել Բակունցի պատմվածքները որպես դպրոցականների գեղագիտական դաստիարակության կարևոր միջոց - Մալխասյան, Էմին
Художественные произведения, включенные в школьные программы, кроме познавательно-воспитательных целей, преследуют также цели развития и развития эстетического вкуса учащихся. В этом отношении очень примечательны рассказы Акселя Бакунца, которые открывают перед читателем неповторимый мир с его красками, людей, стремящихся к гармонии с природой, их радости и драматичных переживаний. В рассказах Акселя Бакунца пейзажи видны во всех пространственных измерениях, они не играют роль всех декораций. Они соответствуют чувствам героев, отражают их эмоции и чувства. Цель данной статьи - раскрыть особенности образности Акселя Бакунца, ведущая задача - представить их учащимся в контексте педагогической мысли, развить у них эстетический вкус, развить умение видеть и ценить прекрасное. Fiction works included in school programs, except cognitive and educational purposes, follow students‘ goals of aesthetic taste and purposes of development. According to this,novels written by Axel Bakunts are significant. They open a unique world to the reader with their colors, people who are looking for harmony with nature, with their happiness and dramatic feelings. Axel Bakunt‘s novels showlandscapes, that are visible in all dimensions and they do not play a decorative role. The novels are consistent withthe feelings of heroes and reflect their emotions. The purpose of this article is to reveal Axel Bakunts‘s imagerypeculiarities. The leading task is to present the novels to schoolchildren in the context of pedagogical thought, to develop their aesthetic taste and the ability to see and value the beauty.
Keywords: Գրականագիտություն